2021
DOI: 10.1111/boc.202100021
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dSTORM super‐resolution microscopy localizes Aurora kinase A/AURKA in the mitochondrial matrix

Abstract: Mitochondria are dynamic organelles playing essential metabolic and signaling functions in cells. Their ultrastructure has largely been investigated with electron microscopy (EM) techniques, which provided a wide range of information on how mitochondria acquire a tissue-specific shape, how they change during development, and how they are altered in disease conditions. However, quantifying protein-protein proximities using EM is extremely challenging. Superresolution microscopy techniques as direct stochastic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…This cluster-like distribution of VDAC1 has also been observed with FLAG-tagged VDAC1 and endogenously immunolabeled VDAC1. 14,15 We demonstrated that VDAC1-clusters are localized at ERmitochondria contact sites using high-resolution fluorescence microscopy. Since studies suggest that VDAC1 is localized at ER-mitochondrial contact sites, 11,12 this finding further indicates that TC-tagged VDAC1 reflects the same localization patterns as endogenous VDAC1.…”
Section: Discussionmentioning
confidence: 92%
“…This cluster-like distribution of VDAC1 has also been observed with FLAG-tagged VDAC1 and endogenously immunolabeled VDAC1. 14,15 We demonstrated that VDAC1-clusters are localized at ERmitochondria contact sites using high-resolution fluorescence microscopy. Since studies suggest that VDAC1 is localized at ER-mitochondrial contact sites, 11,12 this finding further indicates that TC-tagged VDAC1 reflects the same localization patterns as endogenous VDAC1.…”
Section: Discussionmentioning
confidence: 92%